STRUKTUR, MAJAS, DAN KONJUNGSI TEKS CERITA FANTASI KARYA SISWA KELAS VII SMP NEGERI 5 RAMBAH HILIR, KABUPATEN ROKAN HULU, PROVINSI RIAU - Hartendi, Bayu; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT The purpose of this research is to describe these following two things. First, to describe the generic structure of  fantasy story texts by seventh grade students in SMP Negeri 5 Rambah Hilir, Rokan Hulu Regency, Riau Province. Second, to describe the language features  of fantasy story texts by seventh grade students in SMP Negeri 5 Rambah Hilir, Rokan Hulu Regency, Riau Province. The method that is used is descriptive qualitative method. This research was conducted at SMP Negeri 5 Rambah Hilir, Rokan Hulu Regency, Riau Province. The data of the research are fantasy story texts collected in many sources such as the documents of 30 text stories written by the students. The instrument of this research is the researcher himself. Data were analyzed by describing, analyzing, and discussing the data toward the theory. Based on the results of the study, there are two things that can be concluded. First, the  seventh grade students in SMP Negeri 5 Rambah Hilir, Rokan Hulu regency, Riau province have used the third generic structure of fantasy story in writing. The generic structures of  of fantasy story text are orientation, complication and resolution. It is proven by 30 fantasy story texts that have been analyzed, there are 28 fantasy story texts that used generic structure correctly. Second, there are 16 types of figurative languages  were found in writing fantasy story  and 82% accuracies in using conjunctions by the seventh grade students in SMP Negeri 5 Rambah Hilir, Rokan Hulu Regency, Riau Province. Kata kunci: Struktur Teks, Diksi Teks, Konjungsi Teks